C1s targeting antibodies inhibit the growth of cutaneous squamous carcinoma cells - Nissinen, Liisa; Riihilä, Pilvi; Viiklepp, Kristina; Rajagopal, Vaishnavi; Storek, Michael J.; Kähäri, Veli-Matti (Springer Nature, 2025)
Cutaneous squamous cell carcinoma (cSCC) is the most common metastatic skin cancer. The incidence of cSCC is increasing globally and the prognosis of metastatic disease is poor. Currently there are no specific targeted therapies for advanced or metastatic cSCC. We have previously shown abundant expression of the complement classical pathway C1 complex components, serine proteases C1r and C1s in tumor cells in invasive cSCCs in vivo, whereas the expression of C1r and C1s was lower in cSCCs in situ, actinic keratoses and in normal skin. We have also shown that knockdown of C1s expression results in decreased viability and growth of cSCC cells by promoting apoptosis both in culture and in vivo. Here, we have studied the effect of specific IgG2a mouse monoclonal antibodies TNT003 and TNT005 targeting human C1s in five primary non-metastatic and three metastatic cSCC cell lines that show intracellular expression of C1s and secretion of C1s into the cell culture media. Treatment of cSCC cells with TNT003 and TNT005 significantly inhibited their growth and viability and promoted apoptosis of cSCC cells. These data indicate that TNT003 and TNT005 inhibit cSCC cell growth in culture and warrant further investigation of C1s targeted inhibition in additional in vitro and in vivo models of cSCC.